Macrovascular complication phenotypes in type 2 diabetic patients - Papa Giuseppe; Degano Claudia; Iurato Maria P; Licciardello Carmelo; Maiorana Raffaella; Finocchiaro Concetta (Cardiovascular Diabetology, 2013)
Abstract Background Macrovascular diseases (MVD) in type 2 diabetes mellitus (T2DM) are often considered all together, without discriminating the areas involved. The aim of our study was to analyse MVD prevalence in a large population of T2DM patients by dividing the cases into subgroups according to MVD sites (NMVD, no MVD; NSCS, non-significant carotid stenosis; CBVD, cerebrovascular disease; CAD, coronary artery disease; PAD, peripheral artery disease; PVD, polyvascular disease) and studying the anthropometric, clinical and laboratory parameters in each group. Methods A diabetic outpatient cohort (n = 1199) was retrospectively studied. Demographic, clinical and laboratory parameters were included in analyses. A thorough cardiovascular history as documented by previous medical records (including medical and hospital records) and vascular laboratory studies (including standardised electrocardiogram, echocardiogram, provocative tests for cardiac ischaemia, ankle/brachial index, duplex ultrasonography of the carotid and lower limbs and, in selected cases, computed tomography angiography, carotid and peripheral arteriography and evaluation of transcutaneous oxygen pressure), was collected for all of the patients. Standardised procedures were used to assess microvascular complications as well as metabolic syndrome (Mets). Results The unadjusted MVD prevalence was 46.4% among the participants. The majority of patients with MVD were in the PVD group. In the multivariate analysis, age, male sex and diabetes duration were independent risk factors for PAD and PVD (P < 0.01). A low HDL-C value was an independent risk factor in the CAD and PVD groups (P = 0.03). Very high frequencies of MetS were observed in the PAD and PVD groups (94.9 and 95.7% respectively). The most MetS diagnostic criteria were recorded among members of the CAD group (all or all-1 criteria were present in 73% of patients). The average age in the CAD group (64.5 y) was comparable to that of the NMVD group. Microvascular complications were more frequent in the PAD and PVD patients. Conclusion Phenotypic heterogeneity is associated with different macrovascular complications in T2DM patients. These findings might have clinical implications for developing diagnostic and therapeutic strategies targeting type 2 diabetes.